2010
DOI: 10.1021/nn100971s
|View full text |Cite
|
Sign up to set email alerts
|

Direct Low-Temperature Nanographene CVD Synthesis over a Dielectric Insulator

Abstract: Graphene ranks highly as a possible material for future high-speed and flexible electronics. Current fabrication routes, which rely on metal substrates, require post synthesis transfer of the graphene onto a Si wafer or in the case of epitaxial growth on SiC, temperatures above 1000 °C are required. Both the handling difficulty and high temperatures are not best suited to present day silicon technology. We report a facile chemical vapor deposition approach in which nano-graphene and few

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
231
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(248 citation statements)
references
References 20 publications
14
231
0
3
Order By: Relevance
“…Ceramic catalyst25, 31, 53, 74 was proposed as a metal‐free alternative. One of the most promising candidates is γ‐Al 2 O 3 due to its insulating properties, lower adhesion energy to graphene, and reusability as a catalyst 75, 76.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%
“…Ceramic catalyst25, 31, 53, 74 was proposed as a metal‐free alternative. One of the most promising candidates is γ‐Al 2 O 3 due to its insulating properties, lower adhesion energy to graphene, and reusability as a catalyst 75, 76.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%
“…Semiconductors and metal oxides have been reported as the catalysts for the growth of CNTs,44, 45, 46 indicating their possibility as substrates for the growth of graphene. Several reports have shown that graphene‐like films can be synthesized on Si, SiN, Al 2 O 3 , SiO 2 , and MgO 47, 48, 49. However, graphene‐like films grown by these methods normally suffer from poor crystalline quality and coexisting amorphous carbon.…”
Section: Plasma‐enhanced Growth Of 2d Graphenementioning
confidence: 99%
“…3 Nevertheless, the necessity of etching the metal catalyst and transfer of graphene to foreign substrates hampers wide industrialization. Thus, efforts are put into the metal-free growth of graphene on materials including SiO 2 , 4-6 Al 2 O 3 , 7 MgO, 8 etc. To date, however, the graphitization process on dielectrics is poorly understood while the experiments are largely experience based.…”
mentioning
confidence: 99%